2021
DOI: 10.2147/ijgm.s302699
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Opinions and Knowledge About Vaccination in Poland - A Cross-Sectional Observational Study

Abstract: Background and Objectives: Despite the fact that vaccines save many lives worldwide, in many countries, including Poland, the percentage of unvaccinated children is constantly growing. The main reasons for low immunisation coverage include parents' concerns about the safety of vaccines, their fears related to possible adverse events following vaccination, and the increasingly powerful activity of anti-vaccine movements. It is necessary to monitor the public's attitudes to vaccination in order to implement appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…It should be noted, however, that one of the Polish studies [ 17 ] was partially interventional (an interview induced by information presented to the respondent on vaccination and COVID-19). Thus far, apart from the studies discussed above, most of the Polish studies on COVID-19 vaccine hesitancy have focused on selected professional [ 47 , 48 ] and societal groups [ 49 , 50 ]. Our study addresses the problem of vaccine hesitancy in the broadest way through multivariate statistical modeling, and primarily refers to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that one of the Polish studies [ 17 ] was partially interventional (an interview induced by information presented to the respondent on vaccination and COVID-19). Thus far, apart from the studies discussed above, most of the Polish studies on COVID-19 vaccine hesitancy have focused on selected professional [ 47 , 48 ] and societal groups [ 49 , 50 ]. Our study addresses the problem of vaccine hesitancy in the broadest way through multivariate statistical modeling, and primarily refers to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The following Polish studies examined parents’ feelings about recommended vaccines: according to Janosz J. et al, a positive attitude towards the recommended vaccinations was recorded in 60% of the parents who had children under 3 years of age [ 19 ]; according to Lipska E. et al, 44% of surveyed parents had their children vaccinated with at least one recommended vaccine [ 20 ]; according to Pisaniak P. et al, 66.41% of the parents would reach for the recommended vaccinations for their children if they were free of charge. Nevertheless, in that study, respondents who refused to have their children vaccinated would not like to receive the vaccines, even if they were free [ 21 ]. A Polish large survey study revealed that the majority of women wanted to be vaccinated and have their children vaccinated, and considered vaccines to be safe and effective against infectious diseases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of another Polish study show that most parents are aware of the anti-vaccination movements and have a negative attitude towards them, but these movements still influence the public. In addition, the results show a correlation between the level of education and general attitudes towards immunization -people with higher education are more likely to have a negative opinion on this issue [13].…”
mentioning
confidence: 83%
“…Результаты другого польского исследования свидетельствуют о том, что большинство родителей знают о движениях против вакцинации и негативно относятся к ним, но эти движения все еще влияют на общественность. Кроме того, результаты показывают корреляцию между уровнем образования и общим отношением к иммунизациилюди с высшим образованием чаще имеют негативное мнение по этому вопросу [13].…”
Section: Referencesunclassified